Embodied Mind and Neural Underpinnings of the Aesthetic Experience. A Case Study from the German Eighteenth Century: 4E Cognition Theories Forecasted by Johann Gottfried Herder (Global Journal of Medical Research, 2021)
Recent theories within the avenue of the bio-cultural turn, and particularly about embodied cognition are forecasted in the anthropological, philosophical, physiological and scientific debate of the late 18th century in Germany. Philosopher and theologian Johann Gottfried Herder contributed to this discourse sigificantly, opening up new perspectives on the link among thought and language and body. In this paper we aim at highlighting some core issues of Herders's discourse about knowledge, perception and cognition, that seem to anticipate some of the most recent 4E Cognition issues.
Keywords: Embodiment; embodied cognition; anthropology; knowledge; neuroscience